Kaifa Haluka Comic: Facilitating Arabic Language Learning through Innovative and Interactive Technology - Muhammad Luqman Ibnul Hakim Mohd Saad; Mohammed Iqbal Badaruddın; Mohd Baharim Mayidin; Razimi Zakaria; Juaini Jamaludin (Malaysia Journal of Invention and Innovation, 2023)
The progression of information and communication technology has simplified and increased the flexibility of Arabic language learning. It would be a missed opportunity not to fully utilize these advancements. This is where the comic 'Kaifa Haluka' comes in, as it offers a bilingual application in Arabic (transliterated) and English, which has proved to be a valuable resource in teaching and learning Arabic, according to survey results. The comic's interactive element, including the use of QR codes to access videos, has been particularly effective in facilitating learning, and the comic has even won an award for best invention and commercial product at UiTM Kelantan's Invention, Innovation & Design Staff event. It has also been presented at the Invention, Innovation & Design Exposition and received positive feedback from students at UiTM Kelantan, as well as from foreign users such as Arabic language teachers and the public.